Croton maranonensis: a new species of Euphorbiaceae from the tropical inter-Andean dry valleys - Juan Martín-Muñoz; Elienai Cândida e Silva; Paúl Gonzáles; Álvaro Muñoz-Sánchez; Nixon Cumbicus; Zoë Goodwin; Renata Maria Strozi Alves Meira; Ricarda Riina (European Journal of Taxonomy, 2024)
We describe Croton maranonensis Riina & Martín-Muñoz sp. nov., a species in Croton section Julocroton (Mart.) G.L.Webster from the seasonally dry tropical forests and shrublands of the inter-Andean valleys. This species is a small shrub occurring along the Marañón river valley in Peru and similar dry areas in southern Ecuador. We surveyed morpho-anatomical characters of the new species and closely related taxa. To confirm the placement of the new species in C. section Julocroton, we conducted a molecular phylogenetic analysis including three accessions of the new species and selected representatives of section Julocroton and related groups within Croton L. Micro- and macro-morphological evidence, and molecular data support C. maranonensis sp. nov. as an independent lineage within the C. section Julocroton clade. We compared the new species with morphologically similar species in the same section that also occur in the Andean region, including C. flavispicatus Rusby, C. triqueter Lam., and C. hondensis (H.Karst.) G.L.Webster.